JIHAD DALAM KONTEKS DAKWAH KEKINIAN - Dardirie, Achmad (Al-Mishbah: Jurnal Ilmu Dakwah dan Komunikasi, 2020)
This article discusses the essence of the meaning of jihad and its actualization in modern life. Basically, jihad has two meanings; First, jihad with the meaning of Islamic da'wah in a manner that is polite, tolerant, peaceful, and far from coercion and violence. Second, jihad with the meaning of war. Jihad in the first sense must be applied anytime and anywhere, while jihad in the second sense can only be applied under conditions of extreme compulsion due to a certain threat from the enemy. The main purpose of jihad is al-amr bi al-ma ' ruf wa al-nahy an al-munkar. For that, when put in the context of today's modern life, then jihad could be interpreted in the sense of a more macro and holistic, so that all forms of al-amr bi al-ma ' ruf wa al-nahy an al-munkar as an effort to increase the level of education community Islam, an effort to improve the welfare of Muslims, both economically, politically and culturally. All of them fall into the category of jihad in Islam, and are more important than physical jihad with war, because for the current context that is what Muslims need.